The Role of Tax Extension Officers in Optimizing Tax Compliance with Representative Offices - Wahyudi, Slamet (Universitas Serang Raya, 2022)
The debate over the taxation aspect of the Foreign Trade Representative Office (KPDA), especially PPh Article 15, seems to be protracted and will never be finished. Meanwhile, according to the PPh and P3B Laws, KPDAs have fulfilled subjective requirements when they have or occupy an office address where the term establishment still includes a place of management.It is common for a KPDA to carry out marketing activities in the form of product promotion which is carried out continuously for the benefit of the Head Office which is proven to be able to increase and earn export earnings to Indonesia, so that the income is subject to tax in other countries or source countries (Indonesia). only as big as the share of profit that is considered to come from KPDA.The term activities that are purely auxiliary in nature which are additional activities to facilitate essential and significant activities is often the root of the problem so that the KPDA has the right not to pay Article 15 PPh.This study aims to see how the Income Tax Law and P3B regulate income from KPDA, especially business activities that are